Adhesive sheet

By impregnating a specific adhesive into a nonwoven fabric and controlling the physical properties of the adhesive sheet, the challenges of maintaining thickness consistency and adhesion on curved surfaces are addressed, achieving effective adhesion and tracking on complex surfaces.

JP2025043894APending Publication Date: 2025-04-01MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023151460
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing adhesive sheets struggle with maintaining a consistent thickness on curved surfaces, leading to issues such as warping and peeling due to thermal expansion differences between materials like iron, aluminum, and carbon fiber reinforced plastic (CFRP).

Method used

The development of an adhesive sheet made by impregnating a specific adhesive into a nonwoven fabric, with a thickness of 0.2 mm or more, and controlling the physical properties to ensure that the bending stress Q of the adhesive sheet before curing and the adhesive strength P satisfy the formula Q/P ≤ 0.98.

Benefits of technology

This solution enables the adhesive sheet to maintain good tracking properties on curved surfaces and ensure long-term adhesion, addressing the challenges of thickness consistency and thermal expansion differences.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043894000001
    Figure 2025043894000001
  • Figure 2025043894000002
    Figure 2025043894000002
Patent Text Reader

Abstract

To provide an adhesive sheet that has sufficient thickness as an adhesive sheet, exhibits high conformability to a curved surface, and can remain bonded to the curved surface.SOLUTION: An adhesive sheet comprises an adhesive impregnated into a nonwoven fabric, having a thickness of 0.2 mm or more, wherein the bending stress Q of the adhesive sheet before curing and the adhesive strength P of the adhesive sheet before curing satisfy the following formula (1): Q / P≤0.98 (1) (where Q is in units of N / mm2 and P is in units of N / 25 mm).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive sheet, and more particularly to a structural adhesive sheet, particularly a structural adhesive sheet for curved surface bonding useful in the automotive industry. [Background technology]

[0002] Currently, efforts are being made to reduce the weight of car bodies in order to reduce the environmental impact, and in addition to the steel that has traditionally been used, a wide range of materials, primarily aluminum and carbon fiber reinforced plastics (CFRP), are being used in automobiles and other vehicles. On the other hand, when joining dissimilar materials, in addition to compensating for errors in the film thickness of the materials themselves, it is known that if the adhesive layer that bonds the materials together is thin, the materials will warp or peel due to the temperature difference when they are heated or cooled, due to differences in the linear expansion coefficients of the materials.To address this issue, there is a demand for joining that ensures that the adhesive layer is thicker than a certain value in order to relieve stress.

[0003] In the automotive field, adhesives are used in combination with riveting and spot welding, but in recent years, the use of adhesive sheets with a support has increased instead of the adhesive alone, because there is no risk of uneven coating or defects and the coating process can be made more efficient. Such adhesive sheets are used not only for flat surfaces, but also for curved surfaces such as roof panels and B-pillars.

[0004] For example, Patent Document 1 proposes a method of using a thermally expandable adhesive layer to ensure the thickness of the adhesive layer as an adhesive sheet for such applications. Patent Document 2 proposes an attempt to improve conformability to the adherend surface by lowering the storage modulus, and Patent Document 3 proposes a method of inserting a support to ensure the thickness. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 07-145353 [Patent Document 2] JP 2018-197336 A [Patent Document 3] JP 2020-55991 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the adhesive of Patent Document 1 tends to have a low interfacial adhesion between the thermally expandable adhesive and the adherend, and because the thermally expandable layer and the adhesive layer are separate, the adhesive strength tends to be low, posing issues in terms of adhesive reliability, which is important for structural adhesives. Furthermore, the adhesive sheet in Patent Document 2 is made of a resin with a low storage modulus and does not include a support. As a result, when commonly used materials such as iron, aluminum, or carbon fiber reinforced plastics (CFRP) are joined together, the adhesive sheet is unable to withstand the weight, causing the resin in the adhesive sheet to flow and making it impossible to ensure a constant adhesive thickness. In the method of Patent Document 3, the thickness of the adhesive layer is ensured by impregnating the carbon fiber fabric with resin, but there is a problem in that the resistance increases in shapes with a large degree of curvature (large radius), and although it is possible to attach it to a curved surface, it is not possible to maintain that state.

[0007] Therefore, an object of the present invention is to provide an adhesive sheet that has a certain thickness, has good conformability to curved surfaces, and can be maintained in a state where it is attached to the curved surface. [Means for solving the problem]

[0008] However, in light of these circumstances, the inventors conducted extensive research and discovered that the above problems could be solved by combining an adhesive that exhibits specific physical properties before curing with a support that has specific physical properties, thereby controlling the physical properties of the resulting adhesive sheet, and thus completed the present invention. That is, the gist of the present invention is that it has been discovered that by impregnating a support made of nonwoven fabric with a specific adhesive and controlling the physical properties of the resulting adhesive sheet before curing, it is possible to obtain a sheet with good curved surface conformability and to maintain the adhesive sheet adhered to a curved surface for a long period of time, and this has led to the completion of the present invention.

[0009] That is, the present invention has the following aspects. [1] An adhesive sheet obtained by impregnating a nonwoven fabric with an adhesive, the adhesive sheet having a thickness of 0.2 mm or more, and a bending stress Q of the adhesive sheet before curing and an adhesive strength P of the adhesive sheet before curing satisfy the following formula (1): Q / P ≦ 0.98 (1) (However, the unit of Q is (N / mm 2 ) and the unit of P is (N / 25mm). [2] The adhesive sheet according to [1], wherein the adhesive has a storage modulus at 25° C. before curing of 0.0001 to 10 MPa. [3] The adhesive sheet according to [1] or [2], wherein the adhesive comprises a thermosetting resin composition. [4] The adhesive sheet according to [1] or [2], wherein the adhesive contains 50 mass % or more of an epoxy resin. [5] The adhesive sheet according to [1] or [2], wherein the adhesive is solid at 25°C and has a viscosity of 0.1 to 500 Pa s at 100°C. [6] The adhesive sheet according to [1] or [2], wherein the nonwoven fabric is made of glass fiber. [7] The adhesive sheet according to [1] or [2], wherein the volume of the nonwoven fabric contained in the adhesive sheet is 30% or more and less than 100% of the volume of the entire adhesive sheet. [8] An adhesive sheet used in a laminated adhesive sheet in which multiple adhesive sheets are laminated, wherein the adhesive sheet is a nonwoven fabric impregnated with an adhesive and has a thickness of 0.2 mm or more, the laminated adhesive sheet has a thickness of 0.8 mm or more, and the bending stress Q1 of the laminated adhesive sheet before curing and the adhesive strength P1 of the laminated adhesive sheet before curing satisfy the following formula (2): Q1 / P1≦ 0.98 (2) (However, the unit of Q1 is (N / mm 2 ) and the unit of P1 is (N / 25mm). [9] The adhesive sheet according to [8], wherein the adhesive has a storage modulus at 25°C before curing of 0.0001 to 10 MPa.

[10] The adhesive sheet according to [8] or [9], wherein the adhesive comprises a thermosetting resin composition. Effect of the Invention

[0010] The adhesive sheet of the present invention is an adhesive sheet obtained by impregnating a nonwoven fabric with an adhesive, and the thickness of the adhesive sheet is set to be 0.2 mm or more. In addition, the bending stress Q of the adhesive sheet before curing and the adhesive strength P of the adhesive sheet before curing are set to satisfy the above-mentioned formula (1). This makes it possible to achieve both the ability to conform to a curved surface and the ability to maintain the adhesive sheet adhered to a curved surface for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described below based on examples of the mode for carrying out the present invention. However, the present invention is not limited to the embodiment described below.

[0012] In the present invention, when the expression "x to y" (x and y are arbitrary numbers) is used, unless otherwise specified, it includes not only the meaning of "x or more and y or less", but also the meaning of "preferably greater than x" or "preferably smaller than y". When expressed as "x or more" (x is any number) or "y or less" (y is any number), it also includes the meaning that "greater than x is preferable" or "less than y is preferable."

[0013] The term "epoxy resin" is usually used as the name of a category of thermosetting resins or as the name of a category of chemical compounds having one or more epoxy groups in the molecule, but in this specification it is used in the latter sense. In addition, in this specification, the definition of an epoxy resin includes not only polymers having a specific degree of polymerization but also monomers, so long as the compound has one or more epoxy groups in the molecule. In this specification, unless otherwise specified, "molecular weight" means number average molecular weight. In addition, in this specification, "room temperature" means 25°C, and "solid at room temperature (25°C)" means that the softening point is 25°C or higher, or the viscosity at 25°C is 1000 Pa s or higher. In this specification, "liquid at room temperature (25°C)" means that the softening point is less than 25°C and the viscosity at 25°C is less than 1000 Pa·s.

[0014] The adhesive sheet of the present invention is an adhesive sheet obtained by impregnating a nonwoven fabric with an adhesive, wherein the thickness of the adhesive sheet is 0.2 mm or more, and the bending stress Q of the adhesive sheet before curing and the adhesive strength P of the adhesive sheet before curing satisfy the following formula (1): Q / P ≦ 0.98 (1) (However, the unit of Q is (N / mm 2 ) and the unit of P is (N / 25mm).

[0015] The adhesive sheet of the present invention is an adhesive sheet used in a laminated adhesive sheet in which a plurality of adhesive sheets are laminated, the adhesive sheet being formed by impregnating a nonwoven fabric with an adhesive and having a thickness of 0.2 mm or more, the laminated adhesive sheet having a thickness of 0.8 mm or more, and the bending stress Q1 of the laminated adhesive sheet before curing and the adhesive strength P1 of the laminated adhesive sheet before curing satisfy the following formula (2): Q1 / P1≦ 0.98 (2) (However, the unit of Q1 is (N / mm 2 ) and the unit of P1 is (N / 25mm). Each component of the adhesive sheet of the present invention will be described below.

[0016] <<Adhesive>> The resin composition that is the adhesive used in the present invention contains a curable resin that reacts and hardens during adhesion. Such a curable resin is not particularly limited as long as the bending stress Q of the adhesive sheet before curing (bending stress Q1 of the laminated adhesive sheet) and the adhesive strength P of the adhesive sheet before curing (adhesive strength P1 of the laminated adhesive sheet) satisfy the above formula (1). Examples of such a curable resin include epoxy resin, second generation acrylic resin, urethane resin, silicone resin, etc. Among these, from the viewpoints of adhesion to different materials, durability, and heat resistance, thermosetting resins are preferred, and epoxy resins are particularly preferred.

[0017] In other words, the resin composition used as the adhesive in the present invention is preferably an epoxy resin composition containing such an epoxy resin as a main component. Here, in this specification, the "main component" means the component having the highest content (mass%) among the components constituting the adhesive (resin composition).

[0018] The content of the main component in the adhesive (resin composition) is preferably 50% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and most preferably 90% by mass or more.

[0019] Hereinafter, the case where the curable resin is an epoxy resin will be described in detail.

[0020] [Epoxy resin composition] The epoxy resin composition uses an epoxy resin (A) as a curable resin. The epoxy resin (A) preferably contains three components as constituents: a bisphenol A type epoxy resin (A1), a bisphenol F type epoxy resin (A2), and a rubber-modified epoxy resin (A3). The epoxy resin composition usually further contains a curing agent (B), and more preferably contains polymer particles (C) having a core-shell structure, a curing accelerator (D), and an inorganic filler (E), and may also contain other components (G).

[0021] <Epoxy resin (A)> As described above, the epoxy resin (A) preferably contains three components, namely, a bisphenol A type epoxy resin (A1), a bisphenol F type epoxy resin (A2), and a rubber-modified epoxy resin (A3), as constituent components.

[0022] Examples of the bisphenol A type epoxy resin (A1) include commercially available products EPON825, jER826, jER827, jER828, jER834, jER1001 (all manufactured by Mitsubishi Chemical Corporation), Epicron 850 (manufactured by DIC Corporation), Epotohto YD-128 (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.), DER-331, DER-332 (all manufactured by Dow Chemical Japan), Bakelite EPR154, Bakelite EPR162, Bakelite EPR172, Bakelite EPR173, Bakelite EPR174 (all manufactured by Bakelite AG), etc. Among these, jER828 and jER1001 are preferred in terms of the elastic modulus and glass transition temperature of the cured product of the epoxy resin composition.

[0023] The bisphenol A type epoxy resin (A1) may be used alone or in combination of two or more kinds.

[0024] The number average molecular weight of the bisphenol A type epoxy resin (A1) is preferably 200 to 100,000, more preferably 200 to 80,000, and further preferably 200 to 60,000. If the number average molecular weight is too low, the viscosity will be too low, which tends to reduce workability as an adhesive, whereas if the number average molecular weight is too high, the solubility in other monomers will be reduced and the viscosity will be too high, which tends to reduce workability. In this specification, the "number average molecular weight" is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0025] The epoxy equivalent of the bisphenol A type epoxy resin (A1) is preferably 20,000 or less, more preferably 10,000 or less, and further preferably 6,000 or less. If the epoxy equivalent is too high, the solubility in other monomers decreases, and workability during blending tends to decrease. The lower limit of the epoxy equivalent is not particularly limited, but is, for example, 50 or more. In this specification, the "epoxy equivalent" is a value measured in accordance with JIS-K7236:2001.

[0026] The softening point of the bisphenol A type epoxy resin (A1) is preferably 160° C. or lower, more preferably 140° C. or lower, and further preferably 120° C. or lower. If the softening point is too high, the viscosity at room temperature after mixing increases, and the workability as an adhesive tends to decrease. The lower limit of the softening point is not particularly limited, but is, for example, −50° C. or higher. In this specification, the "softening point" is a value measured in accordance with JIS-K7234:2008 (ring and ball method).

[0027] Examples of the bisphenol F type epoxy resin (A2) include commercially available products jER806, jER807, jER4005P, jER4007P, jER4010P, jER1750 (all manufactured by Mitsubishi Chemical Corporation), Epicron 830 (manufactured by DIC Corporation), Epototo YD-170, Epototo YD-175 (all manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.), Bakelite EPR169 (manufactured by Bakelite AG), GY281, GY282, GY285 (all manufactured by Huntsman Advanced Materials, Inc.), etc. Among these, jER806, jER807, and jER4005P are preferred in terms of excellent adhesion after curing of the epoxy resin composition.

[0028] The bisphenol F type epoxy resin (A2) may be used alone or in combination of two or more kinds.

[0029] The number average molecular weight of the bisphenol F type epoxy resin (A2) is preferably 200 to 100,000, more preferably 200 to 80,000, and further preferably 200 to 60,000. If the number average molecular weight is too low, the viscosity will be too low, which tends to reduce workability as an adhesive, whereas if the number average molecular weight is too high, the solubility in other monomers will be reduced and the viscosity will be too high, which tends to reduce workability.

[0030] The epoxy equivalent of the bisphenol F type epoxy resin (A2) is preferably 20,000 or less, more preferably 10,000 or less, and further preferably 6,000 or less. If the epoxy equivalent is too high, the solubility in other monomers decreases, and workability during blending tends to decrease. The lower limit of the epoxy equivalent is not particularly limited, but is, for example, 50 or more.

[0031] The softening point of the bisphenol F epoxy resin (A2) is preferably 160° C. or lower, more preferably 140° C. or lower, and further preferably 120° C. or lower. If the softening point is too high, the viscosity at room temperature after mixing increases, and the workability as an adhesive tends to decrease. The lower limit of the softening point is not particularly limited, but is, for example, −50° C. or higher.

[0032] In addition to the above, commercially available products in which both bisphenol A type epoxy resin (A1) and bisphenol F type epoxy resin (A2) are mixed can also be used, such as jER4250 and jER4275 (both manufactured by Mitsubishi Chemical Corporation).

[0033] The rubber-modified epoxy resin (A3) is, for example, an epoxy-terminated adduct of an epoxy resin with at least one non-crosslinked liquid rubber having an epoxide-reactive group (eg, an amino group or a carboxy group).

[0034] The rubber-modified epoxy resin (A3) may be used alone or in combination of two or more kinds.

[0035] The epoxy resin used as a raw material for the rubber-modified epoxy resin (A3) is not particularly limited, but examples thereof include bisphenol-type epoxy resins, naphthalene-type epoxy resins, biphenyl-type epoxy resins, glycidylamine-type epoxy resins, cyclic epoxy resins, dicyclopentadiene-type epoxy resins, phenol novolac-type epoxy resins, and ortho-cresol novolac-type epoxy resins.

[0036] The non-crosslinked liquid rubber used as the raw material for the rubber-modified epoxy resin (A3) is preferably a homopolymer or a copolymer of a conjugated diene, particularly preferably a conjugated diene / nitrile copolymer. The conjugated diene rubber is preferably butadiene or isoprene, particularly preferably butadiene. The preferred nitrile monomer is acrylonitrile, and the preferred copolymer is a butadiene-acrylonitrile copolymer.

[0037] The glass transition temperature (Tg) of such a non-crosslinked liquid rubber is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower. The lower limit of the glass transition temperature is not particularly limited, but is, for example, −100° C. or higher. In this specification, the term "glass transition temperature" refers to the temperature at the inflection point of a DSC curve obtained by measuring a DSC curve of a sample using a differential scanning calorimeter.

[0038] Such a non-crosslinked liquid rubber preferably has an average of 1.5 to 2.5 epoxide reactive end groups per molecule, and more preferably has an average of 1.8 to 2.2 epoxide reactive end groups per molecule.

[0039] The number average molecular weight of such crosslinked liquid rubber is preferably 500 to 100,000, and more preferably 1,000 to 58,000.

[0040] As the rubber-modified epoxy resin (A3), a carboxy-terminated butadiene nitrile rubber (CTBN)-modified epoxy resin or a nitrile butadiene rubber (NBR)-modified epoxy resin is preferable, and a carboxy-terminated butadiene nitrile rubber (CTBN)-modified epoxy resin is more preferable. Examples of commercially available products include the ADEKA ADEKA Resin EPR series (EPR-1415-1, EPR-2000, EPR-2007, EPR-1630), Momentive EPON Resin 58005 and EPON Resin 58006, and CVC Hypox series (Hypox RA 840, Hypox RA 1340, Hypox RF 1341). Among these, the ADEKA ADEKA Resin EPR series is preferred, and EPR-1630 is more preferred, due to its excellent adhesion and elastic modulus after curing.

[0041] The number average molecular weight of the rubber-modified epoxy resin (A3) is preferably 200 to 200,000, more preferably 200 to 100,000, and even more preferably 200 to 80,000. If the number average molecular weight is too low, the viscosity will be too low, which tends to reduce workability as an adhesive, whereas if the number average molecular weight is too high, the solubility in other monomers will be reduced and the viscosity will be too high, which tends to reduce workability.

[0042] The epoxy equivalent of the rubber-modified epoxy resin (A3) is preferably 10,000 or less, more preferably 7,000 or less, and even more preferably 5,000 or less. If the epoxy equivalent is too high, the soft component does not disperse in the cured product, so that when stress occurs, the stress is concentrated in that area, and the adhesive strength tends to decrease. The lower limit of the epoxy equivalent is not particularly limited, but is, for example, 50 or more.

[0043] The softening point of the rubber-modified epoxy resin (A3) is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 160° C. or lower. If the softening point is too high, the viscosity at room temperature after mixing increases, and the workability as an adhesive tends to decrease. The lower limit of the softening point is not particularly limited, but is, for example, −50° C. or higher.

[0044] The above epoxy resin composition further preferably uses an aromatic ring-containing epoxy resin (A4) that is solid at room temperature (excluding the bisphenol A type epoxy resin (A1), the bisphenol F type epoxy resin (A2), and the rubber-modified epoxy resin (A3)), in terms of low water absorption and the elastic modulus and glass transition temperature of the cured product. Examples of such a resin include a phenol aralkyl type epoxy resin (a commercially available product is "YX7700" manufactured by Mitsubishi Chemical Corporation), a biphenyl type epoxy resin (a commercially available product is "YX4000" manufactured by Mitsubishi Chemical Corporation), and the like.

[0045] The aromatic ring-containing epoxy resin (A4) which is solid at room temperature may be used alone or in combination of two or more kinds.

[0046] The aromatic ring-containing epoxy resin (A4) that is solid at room temperature has a number average molecular weight of preferably 200 to 100,000, more preferably 200 to 80,000, and even more preferably 200 to 60,000. If the number average molecular weight is too low, the viscosity will be too low, which tends to reduce workability as an adhesive, whereas if the number average molecular weight is too high, the solubility in other monomers will be reduced and the viscosity will be too high, which tends to reduce workability.

[0047] The epoxy equivalent of the aromatic ring-containing epoxy resin (A4) that is solid at room temperature is preferably 10,000 or less, more preferably 7,000 or less, and even more preferably 5,000 or less. If the epoxy equivalent is too high, the solubility in other monomers decreases, and workability during blending tends to decrease. The lower limit of the epoxy equivalent is not particularly limited, but is, for example, 50 or more.

[0048] The softening point of the aromatic ring-containing epoxy resin (A4) that is solid at room temperature is preferably 160° C. or lower, more preferably 140° C. or lower, and even more preferably 120° C. or lower. If the softening point is too high, the viscosity at room temperature after mixing increases, and the workability as an adhesive tends to decrease. The lower limit of the softening point is not particularly limited, but is, for example, −50° C. or higher.

[0049] The content of the epoxy resin (A) is preferably from 30 to 100% by mass, more preferably from 40 to 100% by mass, and further preferably from 50 to 100% by mass, based on the total mass of the resin composition.

[0050] The content of the bisphenol A type epoxy resin (A1) is preferably from 0.01 to 70 mass %, more preferably from 0.1 to 60 mass %, and further preferably from 1 to 50 mass %, based on the total amount of the epoxy resin (A).

[0051] The content of the bisphenol F type epoxy resin (A2) is preferably from 1 to 70 mass %, more preferably from 5 to 60 mass %, and further preferably from 10 to 50 mass %, based on the total amount of the epoxy resin (A).

[0052] The content of the rubber-modified epoxy resin (A3) is preferably from 0.01 to 60 mass %, more preferably from 1 to 50 mass %, and further preferably from 5 to 40 mass %, based on the total amount of the epoxy resin (A).

[0053] The content of the aromatic ring-containing epoxy resin (A4) that is solid at room temperature is preferably 0 to 80 mass %, more preferably 1 to 70 mass %, and further preferably 5 to 60 mass %, based on the total amount of the epoxy resin (A).

[0054] The epoxy resin (A) may further contain other epoxy resins other than (A1) to (A4). Specific examples of the epoxy resin (A) include various epoxy resins such as alcohol-type epoxy resins, naphthalene-type epoxy resins, phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, phenol aralkyl-type epoxy resins, biphenyl-type epoxy resins, triphenylmethane-type epoxy resins, dicyclopentadiene-type epoxy resins, glycidyl ester-type epoxy resins, glycidyl amine-type epoxy resins, polyfunctional phenol-type epoxy resins, and aliphatic epoxy resins. These may be used alone or in combination of two or more.

[0055] The epoxy resin (A) preferably contains 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more of an epoxy resin that is solid at room temperature relative to the entire epoxy resin (A). The upper limit of the content of such an epoxy resin that is solid at room temperature is not particularly limited, but is, for example, 100% by mass or less.

[0056] <Hardening agent (B)> The epoxy resin composition usually contains a curing agent (B). Examples of the curing agent (B) include amines, acid anhydrides (carboxylic acid anhydrides), phenols (novolac resins, etc.), mercaptans, Lewis acid amine complexes, onium salts, and imidazoles. Specific examples of the curing agent include those described in Chapter 3 of "Review of Epoxy Resins, Vol. 1 (edited by the Epoxy Resin Technology Association, first edition, published November 2003)" and Chapter 2 of "Review of Epoxy Resins, Recent Progress I (edited by the Epoxy Resin Technology Association, first edition, published March 2009)". Among these, it is preferable to use amines from the viewpoint of adhesion.

[0057] The curing agent (B) may be used alone or in combination of two or more kinds.

[0058] Examples of the amine include aromatic amines such as diaminodiphenylmethane and diaminodiphenylsulfone, aliphatic amines, imidazole derivatives, dicyandiamide, tetramethylguanidine, thiourea-added amines, and their isomers and modified products, etc. Among these, dicyandiamide is particularly preferred in that the epoxy resin composition serving as the matrix has an excellent pot life.

[0059] The content of the curing agent (B) is preferably from 0.01 to 30 mass %, more preferably from 0.1 to 25 mass %, and further preferably from 1 to 20 mass %, based on the total amount of the epoxy resin (A).

[0060] <Polymer particles having a core-shell structure (C)> The epoxy resin composition may contain polymer fine particles (C) having a core-shell structure. The polymer fine particles (C) having a core-shell structure refer to commonly known core-shell type polymers, i.e., polymer fine particles having different molecular structures at the center (core) and the outer periphery (shell).

[0061] Examples of components constituting the core of the polymer particles (C) having a core-shell structure include butadiene rubber (BR), acrylic rubber (ACM), silicone rubber (Si), butyl rubber (IIR), nitrile rubber (NBR), styrene butadiene rubber (SBR), isoprene rubber (IR), ethylene propylene rubber (EPR), etc. Among these, butadiene rubber is preferred.

[0062] The component constituting the shell portion of the polymer fine particles (C) having a core-shell structure is preferably graft polymerized onto the above-mentioned core portion and is covalently bonded to the polymer constituting the core component.

[0063] Examples of components constituting such a shell portion include acrylic acid ester monomers, methacrylic acid ester monomers, and aromatic vinyl monomers.

[0064] Examples of the polymer microparticles (C) having a core-shell structure include commercially available products such as the KANE-ACE series manufactured by Kaneka Corporation (B-11A, B-22, B-561, FM-21, M-701, M-711, M-300, FM-40, M-210, Pa-20, PA101, MR-01, MX-153, MX257, MX154, MX-960, MX-136, MX-965, MX-217, MX227M75, MX-334M75, MX-416, and MX-451), and Metablen manufactured by Mitsubishi Chemical Corporation (Metablen C, Metablen E, Metablen W, and Metablen S).

[0065] Among these, those having a rubber core are preferred from the viewpoints of flexibility and adhesion. The polymer fine particles (C) may be used as they are in particulate form or may be dispersed in other solutions or resins, but from the viewpoint of uniform dispersion in other resins, those dispersed in epoxy resins are more preferred, specifically MX-153, MX-154, MX-136, and MX-267.

[0066] The polymer fine particles (C) having a core-shell structure may be used alone or in combination of two or more kinds.

[0067] The primary particle size of the polymer fine particles (C) having a core-shell structure is preferably 10 to 100,000 nm, more preferably 15 to 50,000 nm, and even more preferably 20 to 10,000 nm, from the viewpoints of elastic modulus, elongation properties, and shear strength of the cured product obtained from the epoxy resin. The primary particle size refers to the volume average particle size of the primary particles, and can be measured, for example, using a Nanotrack particle size distribution analyzer (manufactured by Nikkiso Co., Ltd.).

[0068] In addition, when a dispersion of bisphenol A type epoxy resin (A1) or bisphenol F type epoxy resin (A2) is used for the polymer microparticles (C) having a core-shell structure, the content ratio of (A1) or (A2) in the epoxy resin composition is calculated by adding the content of (A1) or (A2) used in the dispersion.

[0069] The content of the polymer fine particles (C) having a core-shell structure is preferably 0 to 50 mass %, more preferably 1 to 40 mass %, and further preferably 2 to 30 mass %, based on the entire epoxy resin composition excluding the curing agent (B).

[0070] <Curing accelerator (D)> The epoxy resin composition may contain a curing accelerator (D) from the viewpoint of enhancing the curing activity of the curing agent (B). For example, among the curing agents (B), dicyandiamide and the like have a high curing temperature when used alone, so a curing accelerator (D) can be used to enhance the curing activity of dicyandiamide and the like. Examples of the curing accelerator for dicyandiamide include urea derivatives such as 3-phenyl-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), 2,4-diamino-6-(2-methylimidazolyl-(1))-ethyl-s-triazine, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 4,4'-methylenebis(1,1-dimethyl-3-phenylurea), and 2,4-bis(3,3-dimethylureido)toluene, and imidazole derivatives. Among these, urea derivatives are preferred, and 4,4'-methylenebis(1,1-dimethyl-3-phenylurea) is more preferred.

[0071] The content of the curing accelerator (D) is preferably from 0.01 to 30 mass %, more preferably from 0.05 to 25 mass %, and further preferably from 0.1 to 20 mass %, based on the total amount of the epoxy resin composition.

[0072] <Inorganic filler (E)> The epoxy resin composition may contain an inorganic filler (E). Specific examples of the inorganic filler (E) include metal oxides such as aluminum oxide and magnesium oxide, metal carbonates such as calcium carbonate and magnesium carbonate, silicon compounds such as diatomaceous earth powder, basic magnesium silicate, calcined clay, finely powdered silica, and fused silica, metal hydroxides such as aluminum hydroxide, kaolin, mica, quartz powder, glass, ceramics, silicon carbide, graphite, carbon black, carbon nanotubes, molybdenum disulfide, boron, boron nitride, silicon nitride, and aluminum nitride. The inorganic filler (E) may be used alone or in combination of two or more kinds.

[0073] The shape of the inorganic filler (E) is not particularly limited, but is preferably, for example, powdery or spherical, more preferably spherical particles (beads). Among them, it is preferably an ellipsoid with a ratio of short side to long side (short side / long side) of 1 / 2 or less. In addition, the inorganic filler (E) is preferably insulating from the viewpoint of preventing metal corrosion (electrolytic corrosion), and is particularly preferably glass beads.

[0074] The average particle size of the inorganic filler (E) is preferably from 50 to 300 μm, more preferably from 80 to 260 μm, further preferably from 100 to 250 μm, and particularly preferably from 100 to 150 μm, from the viewpoint of adhesiveness. The average particle size can be measured, for example, by an optical microscope or the like. More specifically, the average particle size can be determined by observing the particle sizes of 50 inorganic fillers using a digital microscope and calculating the average value.

[0075] The content of the inorganic filler (E) is preferably 5 to 70 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 10 to 30 parts by mass, based on 100 parts by mass of all the resin components constituting the adhesive. If the content is too low, it tends to be difficult to maintain the film thickness, while if the content is too high, the basis weight of the adhesive sheet increases, making it difficult to use in fields where weight reduction is required.

[0076] <Other Ingredients (G)> The adhesive (resin composition) may contain, as necessary, various additives such as resins other than those described above, dispersants, surfactants, plasticizers, antioxidants, pigments, coupling agents, diluents, flexibility-imparting agents, dispersants, wetting agents, colorants, ultraviolet absorbers, light stabilizers such as hindered amine-based light stabilizers, defoamers, release agents, flow adjusters, and solvents.

[0077] The above other components are preferably contained in an amount of 5% by mass or less based on the entire adhesive (resin composition). On the other hand, the lower limit is not particularly limited, but is usually 0% by mass and may be 0.1% by mass or more.

[0078] <Dispersant> The adhesive (epoxy resin composition) may contain a dispersant. The dispersant means a compound that has the effect of uniformly dispersing the inorganic filler (E) in the adhesive and in the laminate after production. Examples of the dispersing agent include polysiloxane compounds and salts thereof, such as methylhydrogenpolysiloxane, polymethoxysilane, dimethylpolysiloxane, and dimethicone PEG-7 succinate; silane compounds, such as methyldimethoxysilane, dimethyldimethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, dichlorophenylsilane, chlorotrimethylsilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltrichlorosilane, octadecyltrimethoxysilane, octadecyltrichlorosilane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, and 3-acryloxypropyltrimethoxysilane. , 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, hexamethyldisiloxane, 1,1,1,3,3,3-hexamethyldisilazane, 3-carboxypropyltrimethyltrimethoxysilane, etc.); carboxylic acid compounds such as formic acid, acetic acid, butyric acid, lauric acid, stearic acid, oleic acid, 6-hydroxyhexanoic acid, etc.; organic phosphorus compounds such as lauryl ether phosphoric acid, trioctylphosphine, etc.; amine compounds such as dimethylamine, tributylamine, trimethylamine, cyclohexylamine, ethylenediamine, polyethyleneimine, etc., amine carboxylate compounds, and amine phosphate compounds. The term "amine carboxylate compound" refers to a compound having both a carboxyl group and an amino group as functional groups, and the term "amine phosphate compound" refers to a compound having both a phosphate group and an amino group as functional groups. When a dispersant is used in the adhesive (resin composition), one of the dispersants exemplified above may be used alone, or two or more of them may be used in any combination and ratio. A surfactant described below may also function as a dispersant. After production of the laminate, the dispersant may be completely decomposed, partially decomposed, or not decomposed.

[0079] <Surfactant> The adhesive (resin composition) may contain a surfactant. By containing a surfactant, it is possible to prevent the occurrence of dents or uneven drying in the laminate due to the adhesion of minute bubbles or foreign matter during the production of the laminate. Furthermore, the surfactant can improve the wettability of the adhesive. The surfactant is not particularly limited, and known surfactants (cationic surfactants, anionic surfactants, nonionic surfactants) can be used. Among these, silicon-based surfactants, fluorine-based surfactants, and acetylene glycol-based surfactants are preferred. Specific examples of surfactants include a nonionic surfactant such as Triton X100 (manufactured by Dow Chemical Company), a fluorine-based surfactant such as Zonyl FS300 (manufactured by DuPont), silicon-based surfactants such as BYK-310, BYK-320, and BYK-345 (manufactured by BYK-Chemie), and acetylene glycol-based surfactants such as Surfynol 104, Surfynol 465 (manufactured by Air Products), Olfin EXP4036, and Olfin EXP4200 (manufactured by Nissin Chemical Industry Co., Ltd.). In the adhesive of this embodiment, when a surfactant is used, one of the surfactants exemplified above may be used alone, or two or more of them may be used in any combination and in any ratio. After the laminate is produced, the surfactant may be completely decomposed, partially decomposed, or may not be decomposed.

[0080] The storage modulus of the resin composition, which is the adhesive used in the present invention, at 25°C before curing is preferably 0.0001 to 10 MPa, and more preferably 0.001 to 1 MPa. If it is too high, it becomes hard and the adhesion at the interface becomes insufficient, and if it is too low, it tends not to be able to maintain adhesive strength. The storage modulus is the storage modulus measured using a rheometer ("MARSII" manufactured by ThermoFisher Scientific) at a temperature of -20 to 180°C, a heating rate of 3°C / min, a frequency of 1 Hz, and a strain of 0.5%.

[0081] The resin composition that is the adhesive used in the present invention is solid at 25°C and has a viscosity at 100°C of preferably 0.1 to 500 Pa·s, and more preferably 1 to 100 Pa·s. If the adhesive is solid at 25°C, it is easy to prepare a sheet-like adhesive and it can be placed on a nonwoven fabric (support) while maintaining its shape, which makes it possible to improve the uniformity of the adhesiveness in the resulting adhesive sheet. On the other hand, if the viscosity at 100°C is too high or too low, the impregnation ability when the adhesive placed on a nonwoven fabric is impregnated into the nonwoven fabric and the coatability onto a substrate when producing a sheet-like adhesive tend to decrease. The viscosity is measured at 100° C. using a rheometer ("MARSII" manufactured by ThermoFisher Scientific) at a temperature of -20 to 180° C., a heating rate of 3° C. / min, a frequency of 1 Hz, and a strain of 0.5%.

[0082] [Adhesive strength P of adhesive before hardening] The adhesive strength P (N / 25 mm) of the adhesive sheet before curing is usually 0.01 to 30, preferably 0.01 to 20, more preferably 0.01 to 10, particularly preferably 0.01 to 5, and most preferably 0.01 to 1. If it is too high, it tends to be difficult to peel off from the release separator film, and if it is too low, it tends not to be temporarily adhered to the adherend.

[0083] The adhesive strength P (N / 25 mm) of the adhesive sheet before curing can be controlled by, for example, changing the type, compounding ratio, solid content, etc. of the resin that constitutes the adhesive, thereby adjusting the viscosity of the adhesive at room temperature and the glass transition temperature (Tg) before curing, thereby changing the adhesive strength. In addition, the adhesive strength can also be adjusted by compounding a plasticizer and adding, for example, a terpene resin as the plasticizer.

[0084] <<Adhesive manufacturing method>> The adhesive used in the present adhesive sheet can be produced by mixing the respective components. The above-mentioned components are preferably mixed by heating to liquefy some of the epoxy resin and liquefiable components and then mixed. The mixing temperature is preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher. On the other hand, the mixing temperature is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 120°C or lower. If the mixing temperature is below the lower limit, the components tend to solidify, resulting in poor mixing, and if it is above the upper limit, the mixture tends to polymerize and gel during mixing.

[0085] The mixing time is usually 1 minute or more, preferably 10 minutes or more, more preferably 20 minutes or more, and usually 24 hours or less, preferably 18 hours or less, more preferably 12 hours or less. If the mixing time is shorter than the lower limit, uniform mixing tends to be impossible, and if the mixing time is longer than the upper limit, the mixture tends to polymerize and gel during mixing.

[0086] The above components can be mixed by any method that applies a shear force, such as stirring, shaking, kneading, etc., which is generally used for mixing epoxy adhesives. The mixing method is selected according to the physical properties of the adhesive, the production amount, etc. The state of the obtained epoxy adhesive may be either homogeneous or non-homogeneous with particles dispersed therein, and this state is selected according to the application of the adhesive.

[0087] The epoxy adhesive used in the present adhesive sheet is preferably a one-liquid adhesive from the standpoint of ease of handling.

[0088] The curing conditions are not particularly limited, but for example, when a one-component adhesive is used, it is usually heated to a temperature of 80°C or higher, preferably 130°C or higher, and more preferably 150°C or higher, and cured preferably within 60 minutes, and more preferably within 30 minutes, to obtain a laminate in which dissimilar components are bonded together.

[0089] <<Nonwoven fabric>> The nonwoven fabric used as the support of the adhesive sheet is not particularly limited, but is preferably made of synthetic fibers, and in particular, is preferably made of glass fibers because of its excellent dimensional stability, heat resistance, and insulating properties. From the viewpoint of the light weight and resin impregnation of the adhesive sheet, the glass fiber diameter is 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and is preferably 500 μm or less, preferably 100 μm or less, more preferably 50 μm or less. The fiber length is 0.1 mm or more, preferably 1 mm or more, more preferably 10 mm or more, and is 500 mm or less, preferably 100 mm or less, more preferably 50 mm or less. As the binder for the glass nonwoven fabric, for example, polyvinyl alcohol-based synthetic resin, acrylic-based synthetic resin, epoxy-based synthetic resin, melamine-based synthetic resin, vinyl acetate-based synthetic resin, etc. are preferably used. The density of the nonwoven fabric is set to 1.0 g / cm from the viewpoints of improving the resin impregnation in the adhesive sheet, improving the weight of the laminate, and improving the interface adhesion. 3 It is preferable that the content is 0.9 g / cm or less, and more preferable that the content is 0.9 g / cm or less. 3 More preferably, 0.8 g / cm 3 The following is the result. The density referred to here does not mean true density but apparent density, and can be measured by a general method.

[0090] <<Adhesive sheet>> The adhesive sheet is a nonwoven fabric support impregnated with the adhesive. The adhesive sheet may have a release film on at least one of its outermost surfaces, for example, the adhesive is provided on a release film. When the adhesive sheet is laminated between layers of different materials, the release film is peeled off before use.

[0091] As the release film, for example, a PET film, a polyethylene film, a polypropylene film, a fluorine film, a polyimide film, or the like, which has been subjected to a release treatment such as silicone or melamine, can be used.

[0092] The thickness of the present adhesive sheet before thermal curing is 200 μm or more, preferably 200 to 5000 μm, more preferably 300 to 4000 μm, and even more preferably 400 to 3000 μm.

[0093] [Filler content in adhesive sheet] When an inorganic filler (E) is used, the content of the inorganic filler (E) in the present adhesive sheet consisting of the adhesive and the support is preferably 3 to 45 mass %, more preferably 5 to 40 mass %, even more preferably 5 to 30 mass %, and particularly preferably 7 to 20 mass %.

[0094] [Tensile shear adhesive strength] The adhesive sheet preferably has a tensile shear adhesive strength of 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more. When the tensile shear adhesive strength is within the above numerical range, the adhesiveness between different materials is good. From the viewpoint of removability during recycling of the laminate, the tensile shear adhesive strength of the adhesive sheet is preferably 50 MPa or less, more preferably 45 MPa or less, and even more preferably 40 MPa or less.

[0095] The tensile shear adhesive strength can be determined, for example, by the method described in JIS K6850. More specifically, the method is as follows. The adhesive sheet is cut to a width of 25 mm x length of 12.5 mm, and a cold-rolled steel plate (SPCC) of width 25 mm x length 100 mm x thickness 1.6 mm is degreased and washed with ethanol, and then the cut adhesive sheet is inserted between two pieces of SPCC and pressurized to a surface pressure of 1 MPa. The sheet is then placed in a thermostatic chamber and heated at 150°C for 20 minutes to harden the adhesive sheet, producing a peel test piece. The peel test piece produced is subjected to the tensile shear adhesive strength measurement at a speed of 5 mm / min using a tensile tester (Shimadzu Corporation's "Autograph AG-X").

[0096] From the viewpoints of shape retention and local conformity of the adhesive sheet, the volume of the nonwoven fabric contained in the adhesive sheet of the present invention is preferably 30% or more and less than 100% of the volume of the entire adhesive sheet, and more preferably 40% or more and less than 90%.

[0097] [Bending stress Q of adhesive sheet before curing] The bending stress Q (N / mm 2 ) is usually 29 or less, preferably 20 or less, more preferably 10 or less, particularly preferably 5 or less, and most preferably 1 or less. If it is too high, when the surface to be adhered is curved, the adhesive sheet tends not to be able to deform so as to follow the curved surface. Bending stress Q of adhesive sheet before curing (N / mm 2 ) can be controlled, for example, by changing the basis weight and thickness of the nonwoven fabric, and the volume ownership rate of the nonwoven fabric in the adhesive sheet.

[0098] In the adhesive sheet of the present invention, the bending stress Q of the adhesive sheet before curing and the adhesive strength P of the adhesive sheet before curing satisfy the following formula (1). Q / P ≦ 0.98 (1) (However, the unit of Q is (N / mm 2 ) and the unit of P is (N / 25mm). In particular, the above Q / P is preferably 0.6 or less, and more preferably 0.45 or less, and more preferably 0.05 or more. On the other hand, if the above Q / P exceeds 0.98, the bending stress Q of the adhesive sheet becomes too strong, and the adhesive sheet tends not to be able to conform to and continue to hold the curved surface of the adherend. In other words, by setting the Q / P within the above range, when the adherend surface is a curved surface, the adhesive sheet can be attached in a state where it is sufficiently conformed to the curved surface, and can continue to adhere without causing buckling. Therefore, even if multiple adhesive sheets are laminated, a thick multi-layer adhesive sheet can be sufficiently temporarily attached to the curved surface.

[0099] <<Adhesive sheet manufacturing method>> The adhesive sheet of the present invention can be produced, for example, as follows. First, an adhesive (resin composition) having a predetermined physical property is formed into a sheet to obtain a sheet-shaped adhesive. By forming it into a sheet shape, the thickness of the adhesive layer can be made uniform, and unevenness in the application of the adhesive is unlikely to occur, so that the reliability after adhesion is high, and it is particularly useful in production lines that include a process of joining components in a factory.

[0100] Examples of methods for forming the adhesive (resin composition) into a sheet include a method in which the adhesive is laminated or applied onto a base film to obtain a base film / adhesive / base film laminate, and the base film is peeled off when in use. Examples of methods for laminating or applying the adhesive include extrusion lamination such as a T-die, a method using a sheet molding device such as a calendar roll or a double belt press, a comma coating method, a gravure coating method, a reverse coating method, a knife coating method, a dip coating method, a spray coating method, an air knife coating method, a spin coating method, a roll coating method, a printing method, a dip method, a slide coating method, a curtain coating method, a die coating method, a casting method, a bar coating method, and an extrusion coating method.

[0101] Next, the adhesive formed into a sheet shape is, for example, superposed on both sides or one side of a nonwoven fabric of a predetermined thickness, and the adhesive is impregnated into the support made of the nonwoven fabric (impregnation step), thereby obtaining the adhesive sheet of the present invention. That is, the impregnation includes both double-sided impregnation and single-sided impregnation.

[0102] As a method for impregnating the adhesive in the impregnation step, a known method can be used. An example of such an impregnation method is a lamination method in which, in the step of obtaining the above-mentioned sheet-like adhesive, a substrate film on which an adhesive has been provided and a support made of nonwoven fabric are arranged to form a substrate film / adhesive / support made of nonwoven fabric / adhesive / substrate film, or a substrate film / adhesive / nonwoven fabric / support / substrate film, and these are heated and pressed using a vacuum laminator, a calendar roll, a double belt press, or the like to impregnate the nonwoven fabric with the adhesive. Note that the step of impregnating the support made of nonwoven fabric with the adhesive and the step of forming the adhesive into a sheet may be carried out simultaneously or separately.

[0103] Alternatively, instead of forming the adhesive into a sheet, the adhesive may be directly applied to a support made of a nonwoven fabric or laminated thereon to impregnate the nonwoven fabric with the adhesive. Examples of such methods include a comma coating method, a gravure coating method, a reverse coating method, a dip-nip method, a kiss coating method, a spray method, a curtain coating method, etc. Among these, a vacuum laminator, a gravure coating method, and a reverse coating method are preferable.

[0104] In the impregnation step, it is desirable to impregnate the nonwoven fabric with the adhesive while controlling the basis weight, which is the weight per unit area of ​​the nonwoven fabric support. 2 It is preferable to impregnate the support with the adhesive so that the adhesive has a density of 300 to 5000 g / m 2 If the coating weight is too high, the adhesive will tend to leak when curing, whereas if it is too low, the adhesive will tend to dry out.

[0105] In the impregnation step, it is desirable to impregnate the support with the adhesive while controlling the viscosity of the adhesive. It is preferable to impregnate the support with an adhesive whose viscosity has been adjusted to 1 to 500 Pa·s, and more preferably, the viscosity is 10 to 100 Pa·s. If the viscosity is too high, the adhesive tends to flow during impregnation, whereas if the viscosity is too low, the adhesive tends to dry out during impregnation.

[0106] The above viscosity is the viscosity measured using a rheometer ("MARSII" manufactured by ThermoFisher Scientific) at a temperature of -20 to 180°C, a heating rate of 3°C / min, a frequency of 1 Hz, and a strain of 0.5%.

[0107] In the impregnation step, the viscosity of the adhesive can be adjusted without a solvent or with a solvent, but the amount of solvent used when adjusting the viscosity of the adhesive with a solvent is preferably 1 part by mass or less, more preferably 0.1 parts by mass or less, and even more preferably 0.01 parts by mass or less, per 1 part by mass of the adhesive. Most preferably, the adhesive is impregnated into the support without a solvent.

[0108] As described above, by producing an adhesive sheet from a sheet-shaped adhesive, it is possible to improve productivity and reduce energy consumption in terms of the process. In addition, it is possible to reduce unevenness in thickness in terms of the material, and the concentration of local stress on the adhesive surface is reduced, improving the adhesive strength and improving reliability.

[0109] <<Multi-layer adhesive sheet>> The multilayer adhesive sheet obtained by the present invention can be obtained, for example, by preparing a plurality of adhesive sheets of the present invention, stacking them together so that the thickness after curing is 0.8 mm or more, more preferably 1 mm or more, even more preferably 1.2 mm or more, 10 mm or less, more preferably 8 mm or less, even more preferably 6 mm or less, and integrating the adhesive sheets by applying a predetermined pressure and temperature. This can be placed between the surfaces to be bonded, and the surfaces to be bonded can be bonded together by curing the adhesive.

[0110] The adhesive sheet of the present invention and the multilayer adhesive sheet using the same can be suitably used as an adhesive for structural components (panel parts, skeletal parts, suspension parts, etc.) of transportation equipment such as vehicles, aircraft, ships, etc., which require improved strength and weight reduction and which require the use of materials with a relatively large area, i.e., as a structural adhesive (a reliable adhesive that can withstand large loads for long periods of time), and in particular can be suitably used as a structural adhesive for the structural panels of vehicles. EXAMPLES

[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.

[0112] First, the epoxy resin composition for adhesive used in the examples and comparative examples, a sheet-shaped adhesive made by forming this into a sheet, and an adhesive sheet obtained by impregnating a nonwoven fabric with the adhesive were prepared.

[0113] (Epoxy resin composition for adhesives) First, an epoxy resin composition for adhesive use was prepared as follows. That is, 24 parts of bisphenol A type epoxy resin (A1), 32 parts of bisphenol F type epoxy resin (A2), 17 parts of rubber-modified (CTBN-modified) epoxy resin (A3), 20 parts of aromatic ring-containing epoxy resin (A4), and 7 parts of polymer particles (C) having a core-shell structure were mixed and stirred until uniform at 90° C. The mixture was placed in a thermostatic chamber at 70° C. to raise the resin temperature to 70° C., after which 8 parts of curing agent (B) and 2 parts of curing accelerator (D) were added and stirred until uniformly dispersed to obtain an epoxy resin composition for adhesive. This epoxy resin composition for adhesives was solid at 25°C and had a viscosity of 12.8 Pa s at 100°C. In addition, the storage modulus at 25°C was 0.0054 MPa.

[0114] (Sheet adhesive) Next, the obtained epoxy resin composition for adhesive was sandwiched between release PET films (Mitsui Chemicals Tohcello "SPPET100-O1BU", 100 μm) and two sheet-like adhesives (thickness 340 μm) were produced using a laminator. The physical properties of this sheet-like adhesive are shown in Table 1 below. This sheet-like adhesive is also referred to as "Z" in the explanation of the layer structure of the multilayer adhesive sheet described below.

[0115] (Adhesive sheet) Adhesive sheet X After peeling off the release PET film on one side of each of the two sheet-like adhesives, a glass fiber nonwoven fabric support (thickness 380 μm, "SB-050" manufactured by OLIVESTREAM) was sandwiched between the two sheets and laminated to produce an adhesive sheet in which the adhesive was impregnated into the glass fiber nonwoven fabric. The physical properties of this adhesive sheet are also shown in Table 1 below. This adhesive sheet X is also shown as "X" in the layer structure of the multilayer adhesive sheet described below. Adhesive sheet Y An adhesive sheet was produced in the same manner as adhesive sheet X, except that a glass fiber nonwoven fabric (thickness 770 μm, "RAP-110" manufactured by Olivest Co., Ltd.) was used. The physical properties of this adhesive sheet are also shown in Table 1 below. This adhesive sheet Y is also shown as "Y" in the layer structure of the multilayer adhesive sheet described below.

[0116] [Table 1]

[0117] [Example 1] Four sheets of adhesive sheet X were prepared and stacked to produce a laminated adhesive sheet. The laminated adhesive sheet had a layer structure of XXXX and a thickness of 2.73 mm.

[0118] [Example 2] Two sheets of the sheet adhesive and two sheets of adhesive sheet Y were prepared and stacked in the configuration ZYYZ to produce a laminated adhesive sheet. The thickness of this laminated adhesive sheet was 2.99 mm.

[0119] [Example 3] Two sheets of adhesive sheet X and two sheets of adhesive sheet Y were prepared and stacked in a YYXX configuration to produce a laminated adhesive sheet. The thickness of this laminated adhesive sheet was 2.99 mm.

[0120] [Comparative Example 1] Four sheets of adhesive sheet Y were prepared and stacked to produce a laminated adhesive sheet. The laminated adhesive sheet had a layer structure of YYYY and a thickness of 3.07 mm.

[0121] [Comparative Example 2] Eight sheets of sheet adhesive Z were prepared and stacked to produce a laminated adhesive sheet. The layer structure of this laminated adhesive sheet was ZZZZZZZZ, and it did not contain any nonwoven fabric. Its thickness was 2.72 mm.

[0122] For the laminated adhesive sheets prepared in the examples and comparative examples, a shear adhesion test, a bending test of the laminated adhesive sheet before curing, and an adhesion test of the adhesive sheet before curing were performed as described below, and an R-shape conformability evaluation was also performed. These results are shown in Table 2 below.

[0123] <Shear adhesion test> The evaluation method of the shear adhesive strength was carried out in accordance with JIS-K6850. That is, first, the laminated adhesive sheet produced in each Example and Comparative Example was cut to a width of 25 mm × length of 12.5 mm. Next, after degreasing and cleaning a cold-rolled steel plate (SPCC) of width 25 mm × length 100 mm × thickness 1.6 mm with ethanol, the cut laminated adhesive sheet was inserted between two cold-rolled steel plates (SPCC), and in a state where a surface pressure of 1 MPa was applied, the laminated adhesive sheet was placed in a thermostatic chamber and heated at 150 ° C for 20 minutes to harden the cut laminated adhesive sheet, thereby preparing a shear test piece. The prepared shear test pieces were subjected to a tensile shear test at a speed of 5 mm / min using a tensile testing machine (Shimadzu Corporation, "Autograph AG-X") to measure the tensile shear adhesive strength, and were evaluated according to the following criteria. (Evaluation Criteria) ○ 20MPa or more △ 15MPa or more, less than 20MPa × Less than 15MPa Here, for the sheet produced in Comparative Example 2, the resin flowed when pressurized and heated, and the thickness could not be guaranteed, so other tests were not carried out (also omitted from Table 2).

[0124] <Bending Test of Laminated Adhesive Sheet Before Curing> The method for evaluating the bending strength of the laminated adhesive sheet before curing was carried out in accordance with JIS-K7171. That is, first, the laminated adhesive sheets prepared in each example and comparative example were cut to a width of 25 mm respectively to prepare bending test pieces. Then, these bending test pieces were set on a bending testing machine with a lower support distance of 48 mm, and a bending test was carried out under the conditions of a temperature of 23 ± 2°C, a relative humidity of 50% ± 10%, and a speed of 1 mm / min to measure the bending strength (bending stress Q1: N / mm 2 ) of the laminated adhesive sheet before curing.

[0125] <Adhesion Test of Laminated Adhesive Sheet Before Curing> First, the sheet-like adhesive Z was cut into a size of 25 mm in width × 70 mm in length to prepare test pieces. Then, a cold-rolled steel sheet (SPCC) with a width of 25 mm × a length of 150 mm × a thickness of 1.6 mm was degreased and washed with ethanol, and then the above test pieces were pasted. Then, for the pasted test pieces, a 180-degree peel test was carried out at a speed of 100 mm / min using a tensile testing machine ("Autograph AG-X" manufactured by Shimadzu Corporation), and the average of the test forces during the displacement between 60 and 120 mm was taken as the adhesion P1 (N / 25 mm) of the laminated adhesive sheet before curing.

[0126] <R Shape Followability Evaluation> First, the laminated adhesive sheets prepared in each example and comparative example were cut into a size of 2.5 mm in width × 50 mm in length to prepare followability test pieces. Then, along a cold-rolled steel sheet (SPCC) bent to a radius of 8 mm and 98°, the states of the followability test pieces 3 minutes and 15 minutes after pasting were visually observed and evaluated according to the following criteria. (Evaluation Criteria) ○... No back buckling △... Partial back buckling (peeling length less than 25 mm) ×... Back buckling (peeling length 25 mm or more)

[0127] [Table 2]

[0128] The results in Table 2 above show that the laminated adhesive sheets of the Examples have sufficient adhesive strength as structural adhesives, ensure adhesive thickness, and are excellent in curved surface conformability. As can be seen from a comparison between Examples 1 to 3 and Comparative Example 1, when the laminated adhesive sheet satisfies the physical property defined by formula (2), it is found to have excellent curved surface conformability. This is thought to be because the rigidity of the nonwoven fabric allows it to conform to curved surfaces and maintain the shape of the adhesive sheet. Furthermore, as can be seen by comparing Examples 1 to 3 with Comparative Example 2, it is important that the flexural strength of the adhesive sheet is equal to or less than a certain value and that the nonwoven fabric support is impregnated. This is thought to be because by impregnating a nonwoven fabric with a certain bending strength, the resin flows while hardening, and the thickness of the adhesive sheet can be guaranteed, thereby maintaining the adhesive strength. From these findings, it can be said that by impregnating a nonwoven fabric support with an adhesive having specific physical properties to produce an adhesive sheet having specific mechanical properties, it is possible to obtain a thick adhesive sheet that is excellent in all aspects: adhesive strength, guaranteed adhesive thickness, and curved surface conformability. [Industrial Applicability]

[0129] The adhesive sheet of the present invention is applicable to structural adhesive sheets, particularly structural adhesive sheets for curved surface bonding that are useful in the automobile industry.

Claims

1. An adhesive sheet comprising a nonwoven fabric impregnated with an adhesive, The adhesive sheet has a thickness of 0.2 mm or more, An adhesive sheet in which the bending stress Q of the adhesive sheet before curing and the adhesive strength P of the adhesive sheet before curing satisfy the following formula (1). Q / P≦0.98...(1) (However, the unit of Q is (N / mm 2 ) and the unit of P is (N / 25mm).

2. 2. The adhesive sheet according to claim 1, wherein the adhesive has a storage modulus at 25° C. before curing of 0.0001 to 10 MPa.

3. 3. The adhesive sheet according to claim 1, wherein the adhesive comprises a thermosetting resin composition.

4. 3. The adhesive sheet according to claim 1, wherein the adhesive contains an epoxy resin in an amount of 50% by mass or more.

5. 3. The adhesive sheet according to claim 1, wherein the adhesive is a solid at 25° C. and has a viscosity at 100° C. of 0.1 to 500 Pa·s.

6. 3. The adhesive sheet according to claim 1, wherein the nonwoven fabric is made of glass fiber.

7. 3. The adhesive sheet according to claim 1, wherein a volume of the nonwoven fabric contained in the adhesive sheet is 30% or more and less than 100% of a volume of the entire adhesive sheet.

8. An adhesive sheet used in a laminated adhesive sheet in which a plurality of adhesive sheets are laminated, The adhesive sheet is a nonwoven fabric impregnated with an adhesive and has a thickness of 0.2 mm or more, The laminated adhesive sheet has a thickness of 0.8 mm or more, Bending stress Q of laminated adhesive sheet before curing 1 and the adhesive strength P of the laminated adhesive sheet before curing 1 and satisfying the following formula (2). Q 1 / P 1 ≦ 0.98 ・・・(2) (However, Q 1 The unit is (N / mm 2 ) and P 1 The unit is (N / 25mm).

9. The adhesive has a storage modulus at 25° C. before curing of 0.0001 to 10 MPa. The adhesive sheet according to claim 8

10. 10. The adhesive sheet according to claim 8, wherein the adhesive comprises a thermosetting resin composition.

Citation Information

Patent Citations

  • Adhesive material

    JP1995145353A

  • Adhesive composition, sealing sheet, and sealing body

    JP2018197336A

  • Fiber-reinforced adhesive sheet

    JP2020055991A